QUALITY ASSESSMENT OF CERTIFIED TEACHER PERFORMANCE BASED ON CREDIT NUMBER ASSESSMENT SYSTEM AS AN EARLY WARNING SYSTEM - Basar, Abdul (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Certified Teacher Performance Quality Assessment based on the Credit Score Rating System that the average teacher applying for an assessment credit score from the Education Element can meet the requirements of around 85 percent, the Learning Process/Guidance Element is ensured to meet the requirements of around 80 percent, the Element of Continuing Professional Development (PKB) in which there are Scientific Publications and Self-Development of teachers who meet the requirements of only about 60 percent in accordance with a lot of existing literature it seems that teachers have difficulty getting Scientific Publications and Self-Development scores, while Supporting Elements which are not mandatory components must be fulfilled by teachers. Fulfilling the requirements can be 100 percent. Thus, even though the average certified teacher shows a percentage above 70 percent in the elements of Education, elements of the teaching/guidance learning process, and supporting elements, the elements of continuous professional development include components of Scientific Publications and Self-Development, the percentages show in under 70 percent. So with that it is necessary to pay attention to the Early Warning System (EWS), namely the elements of Continuing Professional Development (PKB). So to use improving the quality of teacher performance in Continuing Professional Development (PKB) material, seminars, training and so on are needed for teachers. especially certified teachers. In this way, in the future teachers will be able to compile scientific publications and innovative works without experiencing any more difficulties and of course the self-development of teachers will also automatically increase.